2021
DOI: 10.1007/jhep09(2021)009
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the unbinding of the 𝜙4 kink’s shape mode

Abstract: The 𝜙4 double-well theory admits a kink solution, whose rich phenomenology is strongly affected by the existence of a single bound excitation called the shape mode. We find that the leading quantum correction to the energy needed to excite the shape mode is −0.115567λ/M in terms of the coupling λ/4 and the meson mass M evaluated at the minimum of the potential. On the other hand, the correction to the continuum threshold is −0.433λ/M. A naive extrapolation to finite coupling then suggests that the shape mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In refs. [4,5] it was shown that the same is true of the energies of excited states. These tadpoles do not lead to any inconsistencies.…”
Section: Introductionmentioning
confidence: 83%
“…In refs. [4,5] it was shown that the same is true of the energies of excited states. These tadpoles do not lead to any inconsistencies.…”
Section: Introductionmentioning
confidence: 83%
“…For example, the linear perturbations around the sine-Gordon kink and the φ 4 kink in flat space satisfy Schrödinger-like equations with V PT,− (x; 1, 0) and V PT,− (x; 2, 0), respectively [14][15][16]. The solvability of these potentials makes it possible to give some quantitative discussions on the quantization [3,[14][15][16][17][18] and dynamical collision phenomena of kinks [19][20][21][22][23][24][25][26], see [27] for a comprehensive review. Perturbation equations of some de Sitter thick branes [28][29][30] or black holes solutions [31][32][33][34][35][36][37] are also closely related to the regular PT II potentials.…”
Section: Jhep09(2022)165mentioning
confidence: 99%
“…In this approach, the quantum field is expanded about a classical solution at a fixed base point in moduli space. Besides being manifestly UV finite, the main advantage is that the treatment is fully linear, allowing access to problems [21,22] which would be prohibitively difficult with traditional methods. The limitation is that it can only treat kinks near a base point, which is arbitrary but fixed in each calculation.…”
Section: Introductionmentioning
confidence: 99%

Spectral Walls at One Loop

Evslin,
Halcrow,
Romanczukiewicz
et al. 2022
Preprint
Self Cite